The individual right to training : a modest record - Descamps, Renaud [Verfasser] (My University, 2013)
France introduced the individual right to training (IRT) in 2003/2004, which was intended to help employees play a part in shaping their own career trajectories. This contribution argues that the IRT has not yet achieved the success expected of it. In 2010 only 6.5% of employees took part in training provided under the IRT, and the average number of hours' training undertakten has stagnated at 22. " A lack of information and support for employees may explain this limited success. After all, the mere existence of an individual right is not in itself sufficient to enable workers to avail themselves of it; the context, which determines whether or not circumstances are propitious, is decisive." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; I 2.2.1 Westeuropa; Recht auf Bildung; Betriebliche Weiterbildung; Lebenslanges Lernen; Frankreich